"Working together as a team really gets them fired up": Afterschool program mentoring strategies to promote collaborative learning among adolescent participants. Issue 2 (3rd April 2022) - Yu, Mark Vincent B.; Liu, Yangyang; Hsieh, Ta-yang; Lee, Glona; Simpkins, Sandra D.; Pantano, Alessandra
ABSTRACT: Opportunities for collaborative learning reflect positive peer processes that have strong implications for adolescents' developmental experiences in afterschool programs (ASPs). However, collaborative learning, which involves considering multiple viewpoints and coordinating actions with peers to accomplish a shared goal, is often difficult for adolescents to navigate. Utilizing qualitative methods, the purpose of this study was to identify ASP mentoring strategies that promote collaborative learning among adolescent participants. Based on the experiences and perspectives of college student mentors who serve as frontline staff of a math enrichment ASP for Latino/a middle school students, we identified four mentoring strategies that promote collaborative learning: (1) nurturing personal connections with and among youth, (2) establishing positive group norms, (3) strategically splitting groups and work, and (4) modeling collaborative behaviors. These strategies reflect best practices that frontline staff can utilize to promote adolescents' collaborative learning, skill development, and engagement in ASPs. Practical implications and directions for future research are discussed.